ANALISIS PERMINTAAN ENERGI LISTRIK RUMAH TANGGA (STUDI KASUS : RUMAH TANGGA DI KOTA BENGKULU - Nilman Nilman; Mintargo Mintargo (Universitas Bengkulu, 2019)
This study aims to analyze the factors that influence the demand for electrical energy in households in the city of Bengkulu. With the dependent variable (Y) the demand for electrical energy and the independent variable (X) Income, electricity price/tariff, number of family members. In this study using primary data with a total sample of 100 households in the city of Bengkulu. The data analysis method used is multiple linear regression. From the analysis that has been done the results show that the income variable (X1) has a significant and positive effect on the demand for electricity, electricity prices/tariffs (X2) have a significant and negative effect on the demand for electrical energy and the number of family members (X3) has a significant and positive effect on demand for electrical energy.Keywords: Demand for electrical energy, Electricity price/tariff ,Income, Number of family members.